Desempenho de escolares com e sem transtorno de aprendizagem em leitura, escrita, consciência fonológica, velocidade de processamento e memória de trabalho fonológica - Silva, Cláudia Da (2013)
OBJECTIVE: The objective this study was to compare the performance of students with and without learning disorder in reading, writing, phonological awareness, processing speed and work memory phonological. METHOD: Participated in this study 40 students from 2ª to 4ª grades of elementary education, divided into GI (20 students without learning difficulties) and GII (20 students with learning disabilities). As procedure, we used the tests of reading, writing, phonological awareness, processing speed and work memory phonological of the Test Cognitive-Linguistic Performance - collective and individual version. RESULTS: The results of this study pointed statistically significant differences, suggesting better performance of GI in relation to GII in skills of reading, writing, processing speed and work memory phonological. There was no statistically significant difference in skill of phonological awareness between the groups compared. CONCLUSION: We concluded that the performance of students with learning disabilities in skills of reading, writing, processing speed and work memory phonological showed altered, indicating a limitation in the linguistic performance compared to students without learning disabilities. Concerning the skill of phonological awareness, the students with learning disabilities showed similar difficulty to the group of students without learning difficulties, suggesting that this difficulty is not specific to students with learning disabilities.